Can objective measurements of the nasal form and function represent the clinical picture in unilateral cleft lip and palate?. Issue 5 (May 2017) - Peroz, Roshan; Holmström, Mats; Mani, Maria
Summary: Background: The present study aimed to evaluate the potential correlations between objective measurements of nasal function and self-assessed nasal symptoms or clinical findings at nasal examination among adults treated for unilateral cleft lip and palate (UCLP), respectively. Methods: All UCLP patients born between 1960 and 1987 (n = 109) treated at a tertiary referring center were invited. Participation rate was 76% (n = 83) at a mean of 37 years after the initial surgery. All participants completed the same study protocol including acoustic rhinometry (AR), rhinomanometry (RM), anterior rhinoscopy, and questionnaires regarding self-experienced nasal symptoms. Results: A reduced volume of the anterior nasal cavity on the operated side (measured by AR) correlated to an expressed wish by the patient to change the function of the nose. A similar correlation was seen for the minimal cross-sectional area of anterior nasal cavity on the operated side. Furthermore, correlations were found between smaller volume and area of nasal cavity and a greater frequency of nasal obstruction. No further correlations were found. Conclusion: Objective measurements partly correlate to the clinical picture among adults treated for UCLP. However, these need to be combined with findings at clinical examination and patient self-assessment to represent the complete clinical picture.